The Behaviour of Health Care Providers in Managing Diarrheal Disease in Palembang City, South Sumatera, Indonesia - Rusdi Ismail; Achirul Bakri; Muhammad Nazir; Nancy Pardede (Paediatrica Indonesiana, 1991)
A study on knowledge, attitude and practice of health care providers in Palembang had been conducted at the end of 1989 and beginning of 1990. Four approaches were carried out: (1) by recording the help obtained by cases who consulted researchers for further help for the same diarrheal diseases (DD) episode, (2) by studying the medical records of DD cases admitted to three hospitals, (3) by studying prescriptions dispensed by three pharmacies and (4) by focus group discussions. The findings were analysed to evaluate the achievement of the Indonesian Diarrheal Diseases Control Program (CDD). ORT, avoiding antimotility drugs and appropriated feeding have been accepted and practiced by the providers in Palembang. The target of promotion now is to support the acquisition of these behaviours to be if implemented as a routine habit of the providers and as a part of the ongoing system of health care delivery system. Specifically the danger of loperamide promotion to the policy on antimotility must be stressed. Rapid iv rehydration and avoiding surface precipitating agents have been accepted, but are not practiced consistently yet due to practical considerations. It seems that there is no impact at all of CDD towards the rate of antibiotic therapy in DD. Besides intensifying the campaign, enforcing group pressure, maybe we have to elaborate more the perception of health care provider as a practitioner, and conforming the strategy of the CDD campaign towards the findings. Health education had not been practiced effectively yet. Morale and value system of the providers are important for the success of this program. In general the medical-technic aspect of the CDD has been accepted by the providers, but there is still a lot to do in communicating them to be adopted as an effective behaviour.